2018
DOI: 10.1111/apt.14828
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ileal pouch‐anal anastomosis on graft survival following liver transplantation for primary sclerosing cholangitis

Abstract: In PSC, liver transplantation, colectomy + IPAA is associated with similar incidence rates of hepatic artery thrombosis, recurrent biliary strictures and re-transplantation compared with no colectomy. Colectomy + end ileostomy confers more favourable graft outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 50 publications
1
23
0
1
Order By: Relevance
“…The association between colectomy and PSC was also investigated in a recent study by Nordenvall et al, which showed colectomy prior to PSC diagnosis to be protective against a progressive PSC disease course, although the study did not inform on disease severity and colectomy indication . A recent study by Trivedi et al revealed a colectomy with end‐ileostomy to have a more favourable outcome on graft survival and a protective effect on recurrence of biliary strictures as opposed to ileal pouch‐anal anastomosis or no colectomy . Moreover Joshi et al identified active IBD as a significant predictor for graft failure after liver transplantation .…”
Section: Discussionmentioning
confidence: 99%
“…The association between colectomy and PSC was also investigated in a recent study by Nordenvall et al, which showed colectomy prior to PSC diagnosis to be protective against a progressive PSC disease course, although the study did not inform on disease severity and colectomy indication . A recent study by Trivedi et al revealed a colectomy with end‐ileostomy to have a more favourable outcome on graft survival and a protective effect on recurrence of biliary strictures as opposed to ileal pouch‐anal anastomosis or no colectomy . Moreover Joshi et al identified active IBD as a significant predictor for graft failure after liver transplantation .…”
Section: Discussionmentioning
confidence: 99%
“…A minority of the transplanted PSC/UC patients underwent colectomy (31%). The authors demonstrated a benefit of end ileostomy over IPAA or no colectomy for composite liver graft loss, but not for mortality . Figure 4 captures the most important finding in this paper that may influence clinical decisions for PSC/UC patients and treating physicians .…”
mentioning
confidence: 84%
“…While the authors also looked at outcomes for PSC/UC colectomy for all causes (colitis and dysplasia), there is too large a discrepancy in the number of patients receiving an IPAA or an end‐ileostomy for dysplasia (n = 1 and n = 16, respectively) to draw conclusions for the preferred method of colectomy in this clinical scenario. The authors also demonstrate, in Figure 5, that the end ileostomy group had less PSC recurrence (denoted as recurrent biliary strictures not attributable to HAT) than those without colectomy . While this is indeed interesting information that sheds some light on the potential pathophysiologic link between intestinal microbiota/inflammation and PSC, we should not begin recommending prophylactic colectomy with end ileostomy to all PSC/UC patients requiring a liver transplant just yet.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Along these lines, receiving a colectomy prior to or during liver transplant has been shown to be protective against recurrence of PSC [57]. Other studies have reported that total colectomy with end ileostomy conferred a protective effect against recurrence of PSC post-liver transplant whereas colectomy with an ileoanal pouch formation did not [58]. Overall these studies that once the risk of colonic bacterial translocation is removed, recurrence of PSC is rare, which supports the notion of an underlying infectious etiology as the cause.…”
Section: Recurrent Psc Following Ltmentioning
confidence: 99%